(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article the problem of method of implementation of the picture of nude of man is considered in an interior. The question of decision of space is еxmined in the linage by a linear and air prospect, transmissions of illumination and design of forms of the articles of interior and figure of man by facilities of chiaroscuro taking г account their mutual location and influencing on each other.